Treinamento físico de intensidade moderada como fator preventivo da injúria renal aguda medicamentosa - Esdras Guedes Fonseca (2016)
It is well known that physical training induces cardiovascular adaptations; however, there are few studies reporting possible kidney adaptations, specially in acute kidney injury (AKI). In this study, we investigated the effect of moderate intensity aerobic exercise on the prevention of AKI induced by gentamicin (GM). Experimental procedure was approved by the Ethics Committee on Animal Use (CEUA, Protocol 59 / 2015). Before start training procedure, 28 Wistar rats (250-300 g) underwent a maximal progressive exercise test (MPET). Thereafter, rats were divided into two groups: not trained (NT) and trained (T). The training protocol consisted of running in a treadmill at 65% of maximum speed reached in MPET (60 min/day, 5 days/week for 8 weeks) (T group). NT group also had access to treadmill (5 m/min, 5 min/day, 5 days/week, for 8 weeks). At the end of training, rats were placed individually in metabolic cages and divided into 4 subgroups. NT SAL and T SAL subgroups were injected subcutaneously with 0.9% NaCl (SAL) and NT GM and T GM subgroups were injected with GM (Gentatec ®, 80 mg/kg/day, twice a day, 0.1 ml/100g) for 5 days. Urine and blood samples were collected before and after GM treatment for further renal function analysis. At the end of experiment, rats were sacrificed and kidneys and soleum muscle were collected for further morphological analysis and citrate sinthase assay, respectively. Previous training prevented glomerular filtration rate (GFR) reduction in response to GM. A reduction of 1,561.0 ± 225.0 (NT-SAL) to 512.0 ± 154.0 ml/24h (NT-GM) was much more marked than that observed in T groups (2,634.0 ± 535.0, T SAL, to 1,451.0 ± 185.0 ml/24h, T GM, p<0.05). Both GM and training, per se, increased renal mRNA expression coding for angiotensin I-converting enzyme (ACE). However, previous training prevented the augmentation of renal expression of both ACE and kinin B1 receptor in T GM group. Expression of other RAS and KKS components was unaffected (ACE2 enzyme and AT1, MAS and B2 receptors). The data indicate that physical training has a preventive effect regarding to renal damages induced by GM, possibly and mainly due to interaction with KKS specially reducing B1 kinin receptors expression and/or density in renal tissue.